Sosialisasi Alat Bantu Penangkap Ikan Berdasarkan Permen KP Nomor 18 Tahun 2021 Bagi Nelayan Tambaklorok - Endah Fauziningrum; Andar Sri Sumantri; Irma Shinta Dewi; Ika Nugraha Cahyaning Asmara (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
With a large water area and abundant fisheries and marine resources, fishermen in Indonesia must optimize this potential. Fishermen are one of the stakeholders and guardians of the sea who can utilize marine wealth and ensure the sustainability of Indonesia's marine resources for future generations. Fisheries development must not damage or disrupt the sustainability of fish and marine resources. This article uses a qualitative descriptive method which is carried out by explaining the entire series of community service activities using a field approach. The method used is literature study by searching for and reading references in the form of books, journals, articles and news about fishing gear and their regulations. The material presented in this activity includes 1) Introducing modern and traditional fishing equipment that complies with applicable regulations. 2) Fishermen carry out fishing activities with equipment that complies with regulations so as not to damage the marine ecosystem. Fishermen use tools that are safe for the marine environment and especially in accordance with established rules.